Urban, periurban and horticultural landscapes – Conflict and sustainable planning in La Plata district, Argentina - Baldini, Carolina; Marasas, Mariana Edith; Tittonell, Pablo Adrian; Drozd, Andrea Alejandra (Elsevier, 2023)
Globally, urban areas are expanding onto high-quality agricultural soils and natural environments reducing the area available for food production. The Horticultural Belt of La Plata is one of the main horticultural areas in South America. It is a productive territory that lacks clear spatial planning, resulting in serious socio-environmental problems. Our main objectives were to quantify areas with different land-use aptitude across the region, and to identify areas of potential land-use conflict, detecting those areas that should be prioritized in the development of landscape planning policies. We implement the analytical hierarchy process multicriteria analysis method and a weighted linear combination procedure of factors standardization. We observed a strong influence of urbanization in determining land use in those areas where high/very high aptitude for urbanization and for horticulture overlap. Competition for land use between open field horticulture and greenhouses was observed too. Our research reveals the market influence and the current trend towards intensification of land use that usually prevails in planning strategies. We identified elements that could take part of a multifunctional network of green spaces, made them spatially explicit, and defined a core area for the protection of horticultural production. Finally, we propose recommendations for territorial planning aimed at improving the conditions for the development of more sustainable productive landscapes, a problem that predominates across the world.